Policy Law Criminal Law Against Fulfillment Of The Right To Restitution On Assistant Households (ART) As Victims Of Domestic Violence - Andi Najemi; Sasmiar Sasmiar; Yulia Monita (Jurnal Mamangan, 2025)
This study aims to analyze criminal law policies related to the provision of restitution to domestic workers (ART) who are victims of domestic violence (KDRT). ART's position as domestic workers places them in double vulnerability, both structurally and culturally, due to unequal power relations with employers and limited access to justice. Legal protection for domestic workers as victims of domestic violence can be seen in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT), which only limits perpetrators to imprisonment and fines, while victims (ART) should receive compensation or restitution to restore the losses suffered by the victim. However, the Law on the Elimination of Domestic Violence (PKDRT) does not explicitly regulate the mechanism for granting restitution, so that ART who are victims often do not receive proper recovery, both in terms of material and immaterial. This legal vacuum causes victims' rights to be limited to physical and psychological protection, but does not touch on the aspect of recovering losses due to criminal acts. In fact, restitution is an important instrument from a restorative justice perspective because it places the victim as the main subject whose rights must be restored. This article analyzes how positive law regulates the provision of restitution to domestic workers as victims of domestic violence and the direction and form of future legal regulations (ius constituendum) in providing restitution guarantees for domestic workers as victims of domestic violence. Therefore, a reformulation of criminal law policy is needed by placing restitution not merely as an additional requirement, but as an imperative legal obligation, in order to realize restorative justice and protect domestic workers as a vulnerable group in the Indonesian criminal law system